2014
DOI: 10.1080/09712119.2014.963094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of jackfruit supplement and ageing on the Physico-chemical, texture and sensory characteristics of Chevon patties

Abstract: The study was conducted to evaluate the suitability of using immature jackfruit and chevon meat in emulsion-based products preparation and to assess their quality during refrigerated storage. Chevon meat patties (treatments T2, T3 and T4) were prepared in which chevon meat was substituted with 10%, 20% and 30% immature jackfruit and compared with patties from chevon meat (control T1). The addition of jackfruit in chevon meat patties overall significantly (P < 0.05) influenced proximate analysis, physico-chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…In addition, the cohesiveness and chewiness of BF (100%) were among the lowest, which was at 0.39 and 3.49, respectively. The results were quite similar to the study by Verma et al [19] that showed chevon patties with jackfruit as meat substitute have soft texture compared to the control. This was also parallel with another study of low-fat pork patties with sweet potato powder and added water as fat replacer [22].…”
Section: Colour Measurement and Texture Profile Analysissupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, the cohesiveness and chewiness of BF (100%) were among the lowest, which was at 0.39 and 3.49, respectively. The results were quite similar to the study by Verma et al [19] that showed chevon patties with jackfruit as meat substitute have soft texture compared to the control. This was also parallel with another study of low-fat pork patties with sweet potato powder and added water as fat replacer [22].…”
Section: Colour Measurement and Texture Profile Analysissupporting
confidence: 90%
“…The results also can be compared with the study that uses jackfruit as the meat substitute in chevon patties and contributed to reducing the fat [19]. The reason for reducing fat can be directly related to low-fat content in both jackfruit [19] and breadfruit [20]. The carbohydrate content for patties with BF and JF at 50% were significantly lower (p<0.05) compared to 0%, and 0% and 100%, respectively.…”
Section: Proximate Compositionsmentioning
confidence: 91%
See 1 more Smart Citation
“…Carabeef is red meat that is often viewed as a potential competitor to beef and sheep meat. It is almost universally acceptable and free from culture, tradition, social and economic conditions (Verma et al, 2014 andKhandagale et al, 2013). Some peculiar qualities such as lower in calories, total fat, saturated fat and cholesterol make it suitable for healthconscious people.…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to develop new formulation of nugget which has lower fat content and similar sensory quality compared to the commercially available chicken nugget. The new formulation included jackfruit which has many functional components and has similar sensory properties as chicken [15,16]. Jackfruit not only widely available at reasonable prices on most traditional market and supermarket in Indonesia, but also common in most Javanese home gardens [17].…”
Section: Introductionmentioning
confidence: 99%